Spatial Distribution Characteristics of Soil Water and Salt in Newly Cultivated Farmland Under Gully Control in Loess Hilly Region - Ke Zengming; Ma Lihui; Jiao Feng; Yan Binglong (Shuitu baochi tongbao)
[Objective] Part of the newly cultivated farmland formed by the “Gully Control and Land Reclamation” project is facing the risk of soil salinization in the loess hilly region. The spatial distribution characteristics of soil water and salt and their influencing factors were studied for preventing and controlling soil salinization, and promoting sustainable utilization of newly cultivated land. [Methods] A typical area of newly cultivated land was selected, and six experimental plots were established along a gully head to the gully mouth, with sampling points numbered sequentially from 1 to 6. The grid method was used to obtain soil samples from the 0—20 and 20—40 cm layers in each plot. The multifractal method was used to analyze the spatial distribution characteristics of soil water and salt. [Results] Soil water content and salt content gradually decreased from the gully head to the gully mouth. The mean soil water contents and salt contents at sampling points 1, 2, and 3 were 17.6% and 0.81 g/kg, respectively, which were 23.0% and 14.1% higher than the respective values at sampling points 4, 5, and 6. Meanwhile, the multifractal parameters D1 of soil water and salt at sampling points 1, 2, and 3 were less than the respective values at sampling points 4, 5, and 6. ΔD values showed the opposite result, indicating that the spatial variability of soil water and salt at sampling points 1, 2, and 3 were higher. The depth of groundwater influence was the main reason for increased accumulation of salt in the surface soil at sampling points 1, 2, and 3 (p<0.05). The terrain characteristic was also an important reason (p<0.05). The narrow terrain was not conducive to drainage, was prone to waterlogging, and exhibited exacerbated salt accumulation. In addition, sampling points 1, 2, and 3 may be invaded by slope runoff and sediment with high salt content that increased soil water, salt content, and variability in the area. [Conclusion] The depth of groundwater influence, terrain characteristics, and slope runoff sediment were important reasons for the high soil water content, salt content, and their spatial variability at sampling points 1, 2, and 3 in newly cultivated farmland. Thus, newly cultivated farmland near the gully head location would be a key area for preventing soil salinization in the future.